Thirty years with Flora Croatica database - Nikolić, Toni (2021)
The Flora Croatica (FCD) database records thirty years of continuous work these days. Since the initial limited application, today FCD has been nationally and internationally recognized as the relevant source of verified data on national and regional flora. It is fully web oriented with the strong support of GIS tools in spatial data display and analysis. Users are a wide range of individuals, public institutions, museums, educational system institutions, scientific institutions, and private companies. With numerous interconnected modules, it enables the processing and presentation of various data on flora – taxonomy, nomenclature, distribution, threat status, use, invasiveness, bibliography, collections, etc. Website monitoring indicates great dynamics of data entry, processing, and use, as well as international cooperation. Further development of FCD and application of modern IT tools in the best possible support to all classes of users is expected, both in quantitative and qualitative terms.
Baza podataka Flora Croatica (FCD) bilježi ovih dana trideset godina neprekidnog rada. Od početne ograničene primjene, danas je FCD nacionalno i internacionalno prepoznat kao relevantni izvor provjerenih podataka o nacionalnoj i regionalnoj flori. U cijelosti je web-orijentirana sa snažnom podrškom GIS alata u prikazu i analizi prostornih podataka. Korisnici su široka paleta pojedinaca, javne ustanove, muzeji, ustanove obrazovnog sustava, znanstvene ustanove i privatne tvrtke. S brojnim uzajamno povezanim modulima omogućuje obradu i prikaz raznorodnih podataka o flori – taksonomiju, nomenklaturu, rasprostranjenost, ugroženost, upotrebu, invazivnost, bibliografiju, zbirke i dr. Praćenje prometa ukazuje na veliku dinamiku unosa, obrade i upotrebe podataka, te međunarodnu suradnju. Očekivani je daljni razvoj FCD-a i primjena modernih IT alata u što kvalitetnijoj podršci svim klasama korisnika, u kvantitativnom i kvalitativnom pogledu.
Bibliografija: str. 105-107.
Abstract ; Sažetak.
Keywords: Flora Croatica; Flora -- Baze podataka -- Povijest